Surgical treatment for insular gliomas. A systematic review and meta-analysis on behalf of the EANS neuro-oncology section - Matthias Simon; Anne Hagemann; Sanjana Gajadin; Francesco Signorelli; Arnaud J.P.E. Vincent (Brain and Spine)
Introduction: The appropriate surgical management of insular gliomas is controversial. Management strategies vary considerably between centers. Research question: To provide robust resection, functional and epilepsy outcome figures, study growth patterns and tumor classification paradigms, analyze surgical approaches, mapping/monitoring strategies, surgery for insular glioblastoma, as well as molecular findings, and to identify open questions for future research. Material and methods: On behalf of the EANS Neuro-oncology Section we performed a systematic review and meta-analysis (using a random-effects model) of the more current (2000–2023) literature in accordance with the PRISMA guidelines. Results: The pooled postoperative motor and speech deficit rates were 6.8% and 3.6%. There was a 79.6% chance for postoperative epilepsy control. The postoperative KPI was 80–100 in 83.5% of cases. Functional monitoring/mapping paradigms (which may include awake craniotomies) seem mandatory. (Additional) awake surgery may result in slightly better functional but also worse resection outcomes. Transcortical approaches may carry a lesser rate of (motor) deficits than transsylvian surgeries. Discussion and conclusions: This paper provides an inclusive overview and analysis of current surgical management of insular gliomas. Risks and complication rates in experienced centers do not necessarily compare unfavorably with the results of routine neuro-oncological procedures. Limitations of the current literature prominently include a lack of standardized outcome reporting. Questions and issues that warrant more attention include surgery for insular glioblastomas and how to classify the various growth patterns of insular gliomas.